Perencanaan Keuangan (RAPBS) Rencana Anggaran Pendapatan dan Belanja Sekolah dalam Pengembangan Sekolah di Smk Al Washliyah 9 Perbaungan - Khairani, Khairani; Azmi, Fachruddin; Tambak, Sonia Purba; Syahputra, Dermawan; Siregar, Awaluddinsyah (Fakultas Tarbiyah IAI Nasional Laa Rooiba, 2024)
The draft School Revenue and Expenditure Budget (RAPBS) is carried out through a process of managing school funds, of course involving various parties such as the school principal who regulates financial nets and their management is carried out by treasurers and other components that assist the process of implementing school finances. The purpose of this study was to analyze the implementation of financial planning (RAPBS) school income and expenditure budget plans in school development. This research was carried out with a qualitative approach using descriptive methods. Data collection techniques are observation, interviews and documentation as well as literature studies and group discussions. The results of this research are that the acceptance component of SMK Al Washliyah 9 Perbaungan is optimized by using educational funding sources, namely the existence of regular BOS funds sourced from APBN revenues. Reporting on the accountability of the RAPBS is carried out only to the extent of the school principal. And will be conveyed at the meeting with the parties involved in it. The principal submits a report, especially regarding school financial receipts and expenditures. Evaluation is carried out every quarter or per semester. The conclusion from this study is that good use of the RAPBS has made school development better, including: character education, human resource development and the use of technology. Keywords: RAPBS; Accountability; Development